2018
DOI: 10.3390/w10020197
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Desalination’s Carbon Footprint: The Israeli Experience

Abstract: Given the extraordinary proliferation of seawater desalination plants, Israel's transition to become a country that almost exclusively relies on desalination for municipal water supply is instructive as a case study, especially given concerns about the technology's prodigious carbon footprint. This article offers a detailed description of the country's desal experience with a focus on the associated energy requirements, environmental policies and perspectives of decision makers. Israel's desalination plants ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Strategies to somewhat ameliorate the condition of desiccating lakes have been proposed, though under the pressure of entrenched interests and increasing water stress due to global population growth, the success of these proposals remains uncertain. The government of Israel has discussed the possibility of desalinating Mediterranean Sea water to increase freshwater availability in the basin of the shrinking Lake Kinneret, a solution with a heavy recurrent price tag, large cost in carbon emissions (Tal, 2018), and a range of environmental impacts (Elimelech & Phillip, 2011) that is complicated by the transboundary nature of the Jordan River basin (Wine, 2019a; Wine, 2019c; Wine, 2019e). In the Lake Urmia basin a 40% reduction in water consumption is recommended to partially refill the lake (Alborzi et al, 2018), though the socio‐economic and political feasibility of choosing to allocate water to natural systems over humans at a large scale in the face of water scarcity remains unproven.…”
Section: Resultsmentioning
confidence: 99%
“…Strategies to somewhat ameliorate the condition of desiccating lakes have been proposed, though under the pressure of entrenched interests and increasing water stress due to global population growth, the success of these proposals remains uncertain. The government of Israel has discussed the possibility of desalinating Mediterranean Sea water to increase freshwater availability in the basin of the shrinking Lake Kinneret, a solution with a heavy recurrent price tag, large cost in carbon emissions (Tal, 2018), and a range of environmental impacts (Elimelech & Phillip, 2011) that is complicated by the transboundary nature of the Jordan River basin (Wine, 2019a; Wine, 2019c; Wine, 2019e). In the Lake Urmia basin a 40% reduction in water consumption is recommended to partially refill the lake (Alborzi et al, 2018), though the socio‐economic and political feasibility of choosing to allocate water to natural systems over humans at a large scale in the face of water scarcity remains unproven.…”
Section: Resultsmentioning
confidence: 99%
“…These varying levels of salinity have significant implications for the amount of energy required to desalinate water effectively (Abdelkareem et al, ; Karimi et al, ; Shemer & Semiat, ; Tal, ). As the feedwater's salinity rises, the RO process requires more energy to separate salts from water to overcome higher osmotic pressures (Abdelkareem et al, ; Karimi et al, ; Shemer & Semiat, ; Tal, ). Consequently, solar desalination projects that are large scale and/or involve high salinity feedwater would require commensurately larger solar arrays to compensate for fluctuating solar insolation and the high amounts of energy required (Alsheghri et al, ; Fornarelli et al, ; Karimi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many models that forecast the production of erratic RE sources such as wind and solar power, and these are quintessential to determine the efficacy of investing in these assets to power operations as energy‐intensive as desalination (Adaramola et al, ; Alsheghri et al, ; Delgado et al, ; Fornarelli et al, ; Shahzad et al, ; Tal, ). Both the HOMER and RETScreen models, which the three of the four cases used, offer similar built‐in features and are widely available for public use under license (HOMER Energy, n.d.; Natural Resources Canada, n.d.; Open EI, n.d.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an analysis of the emissions associated with Israeli desalination plants found that the plants are run by onsite natural gas power stations, which have a fairly high carbon footprint. 34 LTTD technology, on the other hand, is capable of achieving a purity of 20-200 ppm which is much better compared to that from membrane techniques. The recovery rate is a function of the temperature differential between the surface and the deeper seawater, with optimum efficiency achieved at a temperature difference of ≥ 20 degrees Celsius.…”
Section: Advantages and Disadvantages Of Membrane And Thermal Distillmentioning
confidence: 99%